Threshold effect of habitat loss on bat richness in cerrado-forest landscapes - Muylaert, Renata L. [UNESP]; Stevens, Richard D.; Ribeiro, Milton C. [UNESP] (Wiley, 2016)
Understanding how animal groups respond to contemporary habitat loss and fragmentation is essential for development of strategies for species conservation. Until now, there has been no consensus about how landscape degradation affects the diversity and distribution of Neotropical bats. Some studies demonstrate population declines and species loss in impacted areas, although the magnitude and generality of these effects on bat community structure are unclear. Empirical fragmentation thresholds predict an accentuated drop in biodiversity, and species richness in particular, when less than 30% of the original amount of habitat in the landscape remains. In this study, we tested whether bat species richness demonstrates this threshold response, based on 48 sites distributed across 12 landscapes with 9-88% remaining forest in Brazilian cerrado-forest formations. We also examined the degree to which abundance was similarly affected within four different feeding guilds. The threshold value for richness, below which bat diversity declines precipitously, was estimated at 47% of remaining forest. To verify if the response of bat abundance to habitat loss differed among feeding guilds, we used a model selection approach based on Akaike's information criterion. Models accounted for the amount of riparian forest, semideciduous forest, cerrado, tree plantations, secondary forest, and the total amount of forest in the landscape. We demonstrate a nonlinear effect of the contribution of tree plantations to frugivores, and a positive effect of the amount of cerrado to nectarivores and animalivores, the groups that responded most to decreases in amount of forest. We suggest that bat assemblages in interior Atlantic Forest and cerrado regions of southeastern Brazil are impoverished, since we found lower richness and abundance of different groups in landscapes with lower amounts of forest. The relatively higher threshold value of 47% suggests that bat communities have a relatively lower resistance to habitat degradation than other animal groups. Accordingly, conservation and restoration strategies should focus on increasing the amount of native vegetation of landscapes so as to enhance species richness of bats.
Keywords: Cerrado; Chiroptera; Conservation; Environmental gradient; Fragmentation threshold; Habitat amount; Interior Atlantic Forest; Landscape resilience